2000
DOI: 10.1159/000012822
|View full text |Cite
|
Sign up to set email alerts
|

Substituting Enzymatically Interesterified Butter for Native Butter Has No Effect on Lipemia or Lipoproteinemia in Man

Abstract: The aim of this study was to determine whether substituting enzymatically interesterified butter for native butter in the usual diet affects lipid and lipoprotein levels in man. Parameters studied were serum total cholesterol, LDL-cholesterol, HDL-cholesterol, free cholesterol, phospholipids, triglycerides, apoA1 and apoB and the fatty acid composition of serum triglycerides, free fatty acids, phospholipids and cholesterol esters. Subjects were healthy volunteers and a controlled design was used. The only math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
(20 reference statements)
2
10
0
1
Order By: Relevance
“…In seven studies, the content of palmitic or stearic acid at sn-2 was increased by the interesterification of experimental fats, while in one study interesterification decreased the sn-2 content of palmitic acid [8]. Studies examining palmitic acid-rich fats used palm oil [9,10], palm olein [11,12], butter [8], or a blend consisting mainly of coconut and palm oil [13]. Two studies have reported the solid fat content at 37 • C; in one study, both the native and interesterified palm oils were liquid [9], while interesterification increased the solid fat content of palm olein from 0 to 6% in the other study [11].…”
Section: Longer-term Effects Of Sn-2 Content Of Palmitic Acid or Steamentioning
confidence: 94%
See 1 more Smart Citation
“…In seven studies, the content of palmitic or stearic acid at sn-2 was increased by the interesterification of experimental fats, while in one study interesterification decreased the sn-2 content of palmitic acid [8]. Studies examining palmitic acid-rich fats used palm oil [9,10], palm olein [11,12], butter [8], or a blend consisting mainly of coconut and palm oil [13]. Two studies have reported the solid fat content at 37 • C; in one study, both the native and interesterified palm oils were liquid [9], while interesterification increased the solid fat content of palm olein from 0 to 6% in the other study [11].…”
Section: Longer-term Effects Of Sn-2 Content Of Palmitic Acid or Steamentioning
confidence: 94%
“…Table 1 summarizes the results. In seven studies, the content of palmitic or stearic acid at sn-2 was increased by the interesterification of experimental fats, while in one study interesterification decreased the sn-2 content of palmitic acid [8]. Studies examining palmitic acid-rich fats used palm oil [9,10], palm olein [11,12], butter [8], or a blend consisting mainly of coconut and palm oil [13].…”
Section: Longer-term Effects Of Sn-2 Content Of Palmitic Acid or Steamentioning
confidence: 99%
“…Several human studies have investigated the effects of consuming IE fats for 3-6 weeks on fasting measures of blood lipids [total cholesterol, high-density lipoprotein cholesterol (HDL-C) and LDL-C; TAG], in comparison with non-IE equivalents. None of these studies reported any significant effect when participants consumed IE palm oil (Zock et al 1995;Nestel et al 1998;Filippou et al 2014b), IE shea butter (Berry et al 2007a), IE butter (Christophe et al 2000), IE lard (Shane et al 1999) or an IE blend of fats (Meijer & Weststrate 1997), relative to a native test fat equivalent. It is possible, though, that the relatively short duration of these trials and the limited number of subjects may have been insufficient to detect a significant effect on fasting lipid profile.…”
Section: What Is Interesterification and Why Is It Used?mentioning
confidence: 99%
“…), IE butter (Christophe et al . ), IE lard (Shane et al . ) or an IE blend of fats (Meijer & Weststrate ), relative to a native test fat equivalent.…”
Section: What Are the Health Effects Of Interesterified Fats?mentioning
confidence: 99%
“…Enfin, des essais cliniques r ealis es chez des sujets sains ou hypercholest erol emiques pendant 3 a 4 semaines, ont montr e que la consommation de graisses interest erifi ees n'avait pas d'impact sur les taux de lipides sanguins (LDL-cholest erol, HDL-cholest erol et triglyc erides a jeun) par rapport a la consommation de graisses natives que ce soient des m elanges d'huiles v eg etales (Meijer et Weststrate, 1997), du beurre de karit e (Berry et al, 2007a), du beurre (Christophe et al, 2000) ou de l'huile de palme (Zock et al, 1995, Nestel et al, 1995.…”
Section: Desunclassified